2020
DOI: 10.3389/fncel.2020.00044
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Dysfunction in Neurological Diseases and Brain Aging

Abstract: Peroxisomes exist in most cells, where they participate in lipid metabolism, as well as scavenging the reactive oxygen species (ROS) that are produced as by-products of their metabolic functions. In certain tissues such as the liver and kidneys, peroxisomes have more specific roles, such as bile acid synthesis in the liver and steroidogenesis in the adrenal glands. In the brain, peroxisomes are critically involved in creating and maintaining the lipid content of cell membranes and the myelin sheath, highlighti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 148 publications
0
27
0
Order By: Relevance
“…Conversely, peroxisomal dysfunction are linked to peroxisome biogenesis disorders. However, the effect of altered pexophagy in neurodegenerative diseases is poorly understood [ 150 ].…”
Section: Selective Autophagy and Its Relevance To Neurodegenerativmentioning
confidence: 99%
“…Conversely, peroxisomal dysfunction are linked to peroxisome biogenesis disorders. However, the effect of altered pexophagy in neurodegenerative diseases is poorly understood [ 150 ].…”
Section: Selective Autophagy and Its Relevance To Neurodegenerativmentioning
confidence: 99%
“…Peroxisomes are evenly distributed in most cells; however, they are largely unknown for muscle cells. On the other hand, peroxisomes are critical for the nervous system as peroxisome dysfunction is associated with several neurological diseases (102). In mouse neurons, peroxisomes are mostly localized within the perinuclear region, but are rarely described in the axons and dendrites (Figure 3) (103).…”
Section: Er and Peroxisome Positioningmentioning
confidence: 99%
“…The integrity and stability of peroxisomes are important for the maintenance of normal mitochondrial function. Peroxisome dysfunction seriously affects mitochondrial metabolism, morphological stability, and biosynthesis, which directly or indirectly lead to rare genetic diseases, such as X-linked adrenoleukodystrophy (X-ALD), acatalasemia, and Zellweger syndrome, and age-related disorders such as PD (Muntau et al, 2000;Pascual-Ahuir et al, 2017;Uzor et al, 2020).…”
Section: Mitochondria Peroxisomes and Pdmentioning
confidence: 99%
“…Peroxisomes have shown interdependency with mitochondria, and experiments have been conducted to investigate possible connections between peroxisomes and PD (Lazarou et al, 2012;Uzor et al, 2020). Lazarou et al reported PD-related PINK1 and parkin ectopic localization to peroxisomes where they initiated pexophagy (Lazarou et al, 2012).…”
Section: Peroxisomes and Mitochondria Relationship With Pdmentioning
confidence: 99%
See 1 more Smart Citation